Optimization of ivacaftor-loaded solid lipid nanoparticles for solubility enhancement - Parihar, Akshay; Prajapati, Bhupendra G.; Paliwal, Himanshu (Frontiers in Pharmacology, 2025)
BackgroundCystic fibrosis (CF) is a systemic disease which primarily affects pulmonary system, but also extends to different important organs to cause multitude of associated diseases, leading to rise in rate of morbidity and mortality. The present investigation is focused on the development and optimization of SLN (Solid Lipid Nanoparticles) formulation of IVF (Ivacaftor) for effective treatment of cystic fibrosis.MethodsIVF-SLN was formulated with the help of homogenization and ultrasonication methods by incorporating Labrasol as liquid lipid, Cetyl palmitate as solid lipid and Polysorbate 20 as the surfactant. The independent variables such as the amount of Lipid (X1) and amount of surfactant (X2) were studied for their effect on dependent variables namely entrapment efficiency and particle size.ResultsThe final formulation of IVF-SLN showed a narrow range in size distribution with the particle size of 150.23 ± 1.59 nm, PDI of 0.256 ± 0.014 and entrapment efficiency of 90.54 ± 1.32%. IVF incorporation into the imperfect crystal lattice was confirmed with the help of a DSC (Differential Scanning Calorimetry) study. The in vitro dissolution study showed improved release pattern from the optimized formulation and release profile followed first-order model indicating a sustained release pattern from lipid matrix.ConclusionThis delivery system presented development of stable nanoparticle formulation exhibiting sustained release pattern, which may contribute to therapeutic outcomes in comparison with drug alone. The outcomes of the research highlighted its potential as an efficient therapeutic strategy for CF management.